PENINGKATAN PENGETAHUAN DAN KETERAMPILAN IBU BALITA STUNTING DALAM PEMBUATAN MPASI LOKAL - Aminah Toaha; Riska Mayang Saputri Ginting; Yosvita Maria Nurmayasari Nurwyn Adam; Ahmad Fahmi Syadzali; Adinda Nur Aini Rofiqoh; Elly Nardyawati; Hana Nurfaizah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
An increase in stunting incidents occurred in Samarinda in 2022. Several studies in the Harapan Baru area found children's inadequate food intake, low environmental sanitation, and low maternal knowledge regarding nutrition. The mother's role is vital in child feeding. Providing nutritional education to mothers of stunted children is carried out to create independence in preparing healthy and nutritious food, as well as protecting children from disease. This community service has the Harapan Baru Community Health Center as a partner. Nutrition education and the formation of a WhatsApp Group were conducted, followed by practice sessions in making complementary food using local ingredients. The results were an increase in the average knowledge of mothers, increasing mothers' skills in preparing adequate complementary food, and improvement in consumption intake after the intervention. Providing education accompanied by cooking practices can be a program intervention in the community to improve mothers' skills in making complementary food